A review on properties and application of bio-based poly(Butylene Succinate) - Shafi, Ayu Rafiqah; Abdan, Khalina; Harmaen, Ahmad Saffian; Mohamed Amin Tawakkal, Intan Syafinaz; Zaman, Khairul; Asim, Mohammad; Norizan, Mohd Nurazzi; Lee, Ching Hao (Multidisciplinary Digital Publishing Institute, 2021)
Researchers and companies have increasingly been drawn to biodegradable polymers and composites because of their environmental resilience, eco-friendliness, and suitability for a range of applications. For various uses, biodegradable fabrics use biodegradable polymers or natural fibers as reinforcement. Many approaches have been taken to achieve better compatibility for tailored and improved material properties. In this article, PBS (polybutylene succinate) was chosen as the main topic due to its excellent properties and intensive interest among industrial and researchers. PBS is an environmentally safe biopolymer that has some special properties, such as good clarity and processability, a shiny look, and flexibility, but it also has some drawbacks, such as brittleness. PBS-based natural fiber composites are completely biodegradable and have strong physical properties. Several research studies on PBS-based composites have been published, including physical, mechanical, and thermal assessments of the properties and its ability to replace petroleum-based materials, but no systematic analysis of up-to-date research evidence is currently available in the literature. The aim of this analysis is to highlight recent developments in PBS research and production, as well as its natural fiber composites. The current research efforts focus on the synthesis, copolymers and biodegradability for its properties, trends, challenges and prospects in the field of PBS and its composites also reviewed in this paper.